D.01 Earlier treatment with the Ketogenic Diet improves seizure outcome in early-onset drug-resistant epilepsy. (17th June 2016) - Irwin, M; Aimola, S; Lowe, H; Liu, Y; Zak, M; Chan, V; Kobayashi, J; Donner, EJ
Abstract : Background: The ketogenic diet (KD) is used to treat severe childhood-onset epileptic encephalopathies, such as Infantile Spasms (IS). Unfortunately, limited resources for KD initiation result in treatment delays. We ask if earlier KD treatment of early-onset drug-resistant epilepsy results in better seizure outcomes.Methods: Children who started KD before age 4 years between 2000-present at SickKids Hospital were identified. Six-month seizure outcome was calculated as percent of pre-diet baseline seizure frequency (BSF).Results: 67 children were identified. 30 (44.8%) started KD <2 years old, 37 (55.2%) started KD 2-4 years old. Among <2 years old group, 83.3% achieved 50% reduction in BSF and 36.7% achieved 90% reduction. Among 2-4 year old group, 62.2% achieved 50% reduction in BSF and 24.3% achieved 90% reduction. 38 children had a history of IS; 17 with IS at diet initiation and 21 with past history of IS. 41.2% of the spasms cohort achieved 90% reduction in BSF, compared to 23.8% of the post-spasms cohort.Conclusions: KD was more effective when started before age 2 years than 2-4 years, and more effective in children with IS than in children with past history of IS. A rapid protocol for KD initiation in young infants and children may improve long-term outcomes